Priests of the Gods: Divination and Leadership in Xenophon - Possi, Florencia Castro (Revista Archai, 2025)
This paper’s goal is to defend the thesis put forward by Michael Flower (2016) that piety is a sine qua non of effective leadership of Xenophon and also justify the fact that the model of leader in Xenophon is "first" (and foremost) a follower of the gods. We will present examples of the use of divination in two main texts. First of all, we will present the advice offered by Xenophon in one of his didactic treatises, the Hipparchicus or Cavalry Commander. This short text was written based on his personal experience as a mercenary soldier and commander and in it he offers his advice on how to become a good commander. In the second place I shall present the practical applications of the counsels of the Hipparchicus in Anabasis, which exhibits one of the most complete descriptions of divination from a first-hand account. Here the main forms of Greek divination are presented: consultation of the oracle at Delphi, extispicine (reading of entrails), omens (interpretation of bird flights), and the appearance of omens of luck or signs.